Effect of Capital Adequency Ratio, Non Performing Financing, and BOPO on Mudharabah Financing - Mohammad Zulman Hakim; Vira Cesaria Nurdiono; Triana Zuhrotun Aulia; Sigit Budi Santoso; Ahmad Zakki; Samino Hendrianto (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to determine whether the influence of Capital Adequency Ratio (CAR), Non Performing Financing (NPF), and Operating Expenses to Operating Income (BOPO) simultaneously or partially affect mudharabah financing in Islamic commercial banks in Indonesia. This study uses secondary data in quantitative form and annual financial reports on each bank's website for 5 years, namely 2017 to 2021. The sampling technique uses a purposive sampling technique, while the statistical test used is panel data regression analysis, as well as the classical multicollinearity test and heteroscedasticity test by considering the hypothesis using Eviews 10. The results show that CAR, NPF and BOPO simultaneously affect mudharabah financing, partially CAR and NPF have no effect on mudharabah financing, while BOPO has a positive effect on mudharabah financing. The coefficient of determination (R2) in this study is 36.6% which indicates that the variables CAR, NPF and BOPO can explain mudharabah financing, the remaining 63.4% can be explained by other variables.